2022
DOI: 10.1093/mnras/stac1070
|View full text |Cite
|
Sign up to set email alerts
|

The escape of globular clusters from the satellite dwarf galaxies of the Milky Way

Ali Rostami Shirazi,
Hosein Haghi,
Pouria Khalaj
et al.

Abstract: Using numerical simulations, we have studied the escape of globular clusters (GCs) from the satellite dwarf spheroidal galaxies (dSphs) of the Milky Way (MW). We start by following the orbits of a large sample of GCs around dSphs in the presence of the MW potential field. We then obtain the fraction of GCs leaving their host dSphs within a Hubble Time. We model dSphs by a Hernquist density profile with masses between 107 M⊙ and 7 × 109 M⊙. All dSphs lie on the Galactic disc plane, but they have different orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Shao et al (2021) showed that accreted globular clusters in the Milky Way and Fornax are less centrally concentrated than those formed in situ. Moreover, globular clusters that escape dwarf satellites of the Milky Way are found orbiting the latter (Rostami Shirazi et al 2022). Piatti et al (2019) derived mean proper motions of the 15 LMC globular clusters, and from existent radial velocities, they computed their velocity vectors.…”
Section: Kinematicsmentioning
confidence: 99%
“…Shao et al (2021) showed that accreted globular clusters in the Milky Way and Fornax are less centrally concentrated than those formed in situ. Moreover, globular clusters that escape dwarf satellites of the Milky Way are found orbiting the latter (Rostami Shirazi et al 2022). Piatti et al (2019) derived mean proper motions of the 15 LMC globular clusters, and from existent radial velocities, they computed their velocity vectors.…”
Section: Kinematicsmentioning
confidence: 99%
“…Belokurov et al 2018;Haywood et al 2018;Helmi et al 2018;Myeong et al 2019;Massari et al 2019;Kruijssen et al 2019;Forbes 2020;Horta et al 2021;Koppelman et al 2019;Naidu et al 2020). Along with the dGals themselves, each of these merger events is likely to have brought in a system of associated globular clusters (GCs) (Searle & Zinn 1978;Mackey & Gilmore 2004;Abadi et al 2006;Law & Majewski 2010;Trujillo-Gomez et al 2021;Rostami Shirazi et al 2022). And while these accreted ★ E-mail: sm2744@cam.ac.uk dGals have long since been disrupted, distributing their constituent stars across the MW, some members of their GC systems have likely remained intact.…”
Section: Introductionmentioning
confidence: 99%